The Sources of Reactive Oxygen Species and Its Possible Role in the Pathogenesis of Parkinson's Disease. (2nd September 2018) - Weng, Minrui; Xie, Xiaoji; Liu, Chao; Lim, Kah-Leong; Zhang, Cheng-wu; Li, Lin
Abstract : Parkinson's disease (PD) is the second most common neurodegenerative disorder characterized by progressive loss of dopaminergic neurons in the substantia nigra. The precise mechanism underlying pathogenesis of PD is not fully understood, but it has been widely accepted that excessive reactive oxygen species (ROS) are the key mediator of PD pathogenesis. The causative factors of PD such as gene mutation, neuroinflammation, and iron accumulation all could induce ROS generation, and the later would mediate the dopaminergic neuron death by causing oxidation protein, lipids, and other macromolecules in the cells. Obviously, it is of mechanistic and therapeutic significance to understand where ROS are derived and how ROS induce dopaminergic neuron damage. In the present review, we try to summarize and discuss the main source of ROS in PD and the key pathways through which ROS mediate DA neuron death.